Fostering Humanism and Professionalism in Pediatric Residency Training - Jennifer Kesselheim; Katharine Garvey; Theodore Sectish; Robert Vinci (Association of American Medical Colleges, 2010)
Abstract The residency experience presents trainees with many challenges that conspire to suppress compassion and empathy. As a result, residents are at risk for depression and burnout, and educators must seek new curricular elements to foster humanism and professionalism in residency training. Additionally, the teaching of professionalism is required by the ACGME and encouraged by the American Board of Pediatrics. We developed a case-based discussion curriculum for the Boston Combined Residency in Pediatrics, which was implemented in September 2007. The curriculum aims to support residents, allow them time to reflect on their doctoring, and foster the development of coping strategies. Pediatric interns and junior's classes are each divided into small groups of 10-12, and all groups have two to three faculty facilitators. Groups remain constant over time to create continuity and a safe environment for discussion. The groups convene monthly, September through June, in place of the regular noon conference. Residents receive readings from the artistic medical literature prior to each session. During each session, participants read aloud a case vignette highlighting one of the many challenges to humanism and professionalism. The vignette is used as a reflective trigger for ensuing discussion. Feedback is collected from facilitators and residents after each session. The curriculum has received overwhelmingly positive feedback from residents, facilitators, and residency leadership. We request that resident participants and group facilitators complete feedback forms, which ask about the usefulness of the case vignette; relevance of the session topic; opportunities for reflection, communication, and identification of coping skills; and whether the session represents an important facet of the overall teaching curriculum. Feedback data indicate that the most influential and appreciated aspect of the curriculum is the continuity and sense of community afforded by the small groups. Time and again residents have commented that coming together with a consistent group of classmates to communicate about experiences the group shares is enlightening and meaningful.